PENGARUH CUSTOMER EXPERIENCE DAN SERVICE QUALITY TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada The Praja Coffee & Resto) - Ida Bagus Nyoman Udayana; Agus Dwi Cahya; Fransizka Ayu Kristiani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of customer experience and service quality on customer loyalty with customer satisfaction as an intervening variable at The Praja Coffee & Resto. The data used in this study are primary data and quantitative research methods with a sample of 102 respondents. using a sampling technique in the form of accidental sampling. Data was collected by sending a questionnaire link that was sent online to respondents. The data were analyzed using the IBM SPSS application. The results showed that customer experience and service quality variables had a positive and significant effect on customer loyalty and customer satisfaction. The customer satisfaction variable also has a significant positive effect on the customer loyalty variable. The customer satisfaction variable is able to mediate the customer experience and service quality variables on the customer loyalty variable.